Plato’s Phaedo and “the Art of Glaucus”: Transcending the Distortions of Developmentalism - Furness Altman, William Henry (Revista Archai, 2021)
In a 1985 article, Diskin Clay offered a modern solution to an ancient problem: instead of choosing between the scholiast’s two different explanations of “the art of Glaucus,” he offered a more textual explanation based on Socrates’ image of the distorted appearance of the embodied soul in Republic X. This paper’s thesis is that we should reconsider the way we read Socrates’ last discourse by privileging its dramatic and didactic aspects in a manner that allows us to give Clay’s insights the weight they deserve. This is preferable to regarding Phaedo as an outgrown stage of Plato’s development rather than the dramatic culmination of the dialogues as a whole, and the hegemonic hermeneutic based on chronological order of composition has made this great dialogue’s original form as unrecognizable as the ocean has made Glaucus.